Cells of the Immune System - Fuchs, Ota; Shamsadin Athari, Seyyed (IntechOpen, 2020)
The cells of the immune system are lymphocytes (T-cells, B-cells and NK (natural killer) cells), neutrophils, eosinophils, and monocytes/macrophages. This book is an overview of some types of these cells and their role in recognizing and/or reacting against foreign material. The immune system is characterized by collaboration between cells and proteins. The development of all cells of the immune system begins in the bone marrow with a hematopoietic stem cell. Two chapters deal with neutrophils, three chapters with T-cells, four chapters with eosinophils, and other chapters review the immunomodulation of macrophages, the role of transcription factor KLF4 in regulating plasticity of myeloid-derived suppressor cells, immune reconstitution after allogeneic hematopoietic stem cell transplantation, and role of sorption detoxification in the therapy of acute radiation sickness.